Impacts of Limestone Particle Size on the Performance of Flexible Wood Fiber Composite Floor - Hongcheng He; Jinling Nie; Jing Wang (Advances in Materials Science and Engineering)
Sustainable wood floor (WFF), produced from natural plants, is a sort of novel green and ecofriendly composite floor, which has been attracting more and more attention in the world. WFF also gives a solution of utilizations of agricultural wastes, such as bamboo mats and hemp hurd. The additive limestone powder plays key role in the performance of flexible bamboo composite floor, so, in this paper, the effects of limestone size and size distributions were investigated. The best particle size distributions of limestone are 25 wt% of 48 μm, 25 wt% of 106 μm, and 50 wt% of 160 μm. The as-obtained WFF has good elasticity, good affinity, and strong comfortableness as well as free formaldehyde release.